A desconsideração da personalidade jurídica e a aplicabilidade no processo falimentar - Cardoso, Tadeu Santos (2023)
The core of this research is to verify the application of the disregard of legal entity in judicial practice and examine the tracing of hermeneutic lines in order to enable the application to be made respecting the constitutional principles, which dictate the infraconstitutional interpretation, examining the aspect prescribed by Law nº 14112/20. The problem, therefore, consists in seeking interpretations that are in line with the guiding constitutionalization of Private Law, as well as allow for greater effectiveness in the forensic daily life. In view of such problematic, it is understood, as the most feasible hypothesis, that the disregard is in line with the guidelines of the Citizen Charter, and the interpreter, supported by the hermeneutic principle of maximum effectiveness, should seek to extract from the normative provision a greater plexus of effects, respecting the limits of the infra-constitutional text, avoiding that the rule in question becomes useless from the legal point of view, expropriating it from the possible and possible developments in the forensic practice. Thus, the present research has as its general objective to seek viable solutions to avoid the impediment to the application of the traditional institute in the dynamics of insolvency, making available the means and alternatives so that a more effective application can be achieved with fincas on the dotted foundation, the respect for the lines of colmatation; and the specific objectives are set in its realization in the judicial sphere, more specifically in the control to be made by the judicial activity, based on procedural issues proceduralized by the Civil Procedure Code of 2015 (CPC/15), now nuanced by Law nº 14. 112/20. The approach to the theme will be made through the dialectical method, through the analytical-bibliographical study with jurisprudential contextualizations, especially from the Citizenship Court, all related to the researched theme. In the end, it is understood that the relevance of the study concerns the hermeneutic alternatives that make the application of the legal figure viable, in order to make it compatible with the dictates of the CF/88, especially the social function of the property (art. 5, XXIII), aiming at the deepening of the discussions around the intriguing inquiries that plague this specific theme.